Clinically important immunological processes in acute and fulminant hepatitis, mainly due to hepatitis B virus. Issue 4 (April 1982) - Mackenjee, M K; Kiepiela, P; Cooper, R; Coovadia, H M
Abstract : Clinically useful criteria were found by studying immunological functions on admission in 15 African children with acute hepatitis (AH) (11 of whom were HBsAg positive) and in 11 children with fulminant hepatic failure (FHF) (8 of whom were HBsAg positive), and by comparing these results with normal controls. Nine of the FHF patients died. All the AH patients survived despite the development of transient liver failure in seven. There was significant diminution of components of the classical and alternative pathways of complement and total haemolytic complement in FHF compared with AH, and in both groups in comparison with controls. Cellular immunity tested by phytohaemagglutinin and HBsAg transformation of lymphocytes and leucocyte migration inhibition with HBsAg, were more impaired in FHF than AH. These indices were reduced in both groups of patients compared with controls. The most important index correlating with severity of clinical disease was C3. It was lowest in FHF, but within this group was highest in 2 patients who survived, and in AH the C3 on admission was significantly lower in patients who subsequently showed signs of transient liver failure than in those who did not. The prothrombin index was less sensitive in differentiating serious from mild illness. It is suggested that C3 levels can be helpful in monitoring patients with acute liver disease.